2022
DOI: 10.1021/acsami.2c05286
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Fabrication of Magnetic and Hierarchically Porous Carbon Films for Efficient Electromagnetic Wave Shielding and Absorption

Abstract: Carbon-based materials have been recognized as a promising method to eliminate electromagnetic interference (EMI) shielding and electromagnetic (EM) wave absorption. However, developing lightweight, ultrathin, and efficient EM wave-shielding and wave-absorbing materials remains a challenge. Herein, a series of magnetic porous carbon composite films with a hierarchical network structure were fabricated via pyrolysis of porous polyimide (PI) films containing magnetic metallic salts of Fe­(acac)3 and Ni­(acac)2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…A structural and electrical relationship establish between amorphous carbon and graphene in deposited carbon films by hot filament CVD [41]. A recent study investigates porous carbon films for efficient electromagnetic applications [42]. Vertical mesoporous carbon films were investigated by studying their electrochemical sensors application [43].…”
Section: Of 27mentioning
confidence: 99%
“…A structural and electrical relationship establish between amorphous carbon and graphene in deposited carbon films by hot filament CVD [41]. A recent study investigates porous carbon films for efficient electromagnetic applications [42]. Vertical mesoporous carbon films were investigated by studying their electrochemical sensors application [43].…”
Section: Of 27mentioning
confidence: 99%
“…39,40 Among them, carbon aerogels have aroused a wide interest due to their 3D pore structure, continuous conductive matrix, low density, and electrical conductivity. 41,42 In addition, two-dimensional transition metal (MXene) films have also received broad attention in recent years due to their extraordinary conductivity (5.8 × 10 4 S•m −1 ), 43 which could turn out over 60 dB EMI SE for foam and textiles. 44−46 For example, Zong et al reported that MXene-derived titanium carbon nanotubes (CNT) and cellulose-derived carbon aerogels were prepared by grafting, freeze-drying, and pyrolysing, which achieves an efficient EMI shielding effect of 72.9 dB.…”
Section: Introductionmentioning
confidence: 99%
“…The EM shielding and absorbing ability of composite materials can be effectively enhanced by adjusting the distribution of their conductive components and structures. Hence, it is an effective strategy to reduce the impedance mismatch by constructing a porous conductive network to reduce R and SE R values, such as conductive air gel, foam, and 3D braided fabric. , Among them, carbon aerogels have aroused a wide interest due to their 3D pore structure, continuous conductive matrix, low density, and electrical conductivity. , In addition, two-dimensional transition metal (MXene) films have also received broad attention in recent years due to their extraordinary conductivity (5.8 × 10 4 S·m –1 ), which could turn out over 60 dB EMI SE for foam and textiles. For example, Zong et al reported that MXene-derived titanium carbon nanotubes (CNT) and cellulose-derived carbon aerogels were prepared by grafting, freeze-drying, and pyrolysing, which achieves an efficient EMI shielding effect of 72.9 dB …”
Section: Introductionmentioning
confidence: 99%
“…The obtained PI foams usually consist of aromatic structures which render the foams with advanced high temperature resistance, flame retardancy, and radiation resistance properties. Numerous efforts have focused on improving the mechanical properties of PI foams by modifying their molecular structures. , Li et al , introduced a rigid 2-(4-aminophenyl)-5-aminobenzimidazole (BIA) monomer with higher rigidity into the PI molecular chains. With increasing BIA content, smaller and closed cells were obtained, and the density of the prepared PI foam could be controlled in the range of 20–100 kg·m –3 .…”
Section: Introductionmentioning
confidence: 99%